Operationalization and assessment of conceptions of teaching - Chan Choon Hian (Adult Education Research Conference, 1993)
Conceptions of teaching are representational models which people hold concerning teaching. An instrument, Conceptions of Teaching Scale (CTS) was developed to operationalize and assess conceptions of teaching of adult instructors. The instrument was found to be valid and reliable